Hyperstition Bot (Or, An Evolutionary Machine Appropriating Human Culture) - Koutsomichalis, Marinos (My University, 2019)
'Hyperstition Bot (Or, An Evolutionary Machine Appropriating Human Culture)' consumes the web footprint of human culture, appropriates it, and produces own digital content in an unattended fashion and with respect to evolutionary algorithms, natural language processing/understanding, machine learning, machine listening/vision, and audio/video/3D-model synthesis. Crawling the WWW for media content of all sorts, it retrieves digital instances of human culture and (employing a series of intelligent comprehenders and synthesisers) it algorithmically generates audio, video, image, text, and 3D data. In this way, it ever transfigures, re-synthesises, remmediates, and re-appropriates human culture with respect to congenital cybernetic orderings, to bring forth and to actualise a hybrid, multimedia, multilingual, multi-religious, post-geographical, post-political, techno-magical, and, ultimately, ‘hyperstitional’ computational reality.
Keywords: Art